Innovation system in air transport management (Journal of Information Systems and Technology Management, 2019)
Identifying previous research subjects on innovation management in air transport provides not only updated references on new technologies in this industry, but also indicates which areas need to be prioritized in future research. A systematic literature review of publications in this field over the past decade, from 2005 to 2015, including 2016 publications in progress, was carried out, adopting as a control document the proceedings from the 19th ATRS World Conference, held in Singapore in 2015. The searches were done on ScienceDirect and included reports from over 2,500 journals. The abstracts, titles, and keywords were considered, and Boolean connectors were used. The term “innovation” was combined with at least one of eight different strings: air* (e.g., airport, airline, and aircraft), flight, transport, aviation, carrier, lcc, fsc and seat, which were identified as the terms with the highest frequency of incidence in the 129 files in the control document. From the 731 articles identified and analyzed, 92 were considered as directly related to innovation management in air transport. The results showed that the areas with a higher incidence of studies were the aircraft industry (energy efficiency, industrial process, and noise and pollutant emission reduction), airlines (business model, IT and planning and management), policies (sustainable transport, incentive mechanisms and societal aspirations), and airport (services, security, self-financing and air traffic control and projects). From this review, it was determined that, in addition to the limited studies on this subject, there is also a lack of research on innovations in airport structure, such as runway pavements and the optimization of airport sites, as well as on new forms of disposal of wastes generated during the flight, crew training and integrated innovation planning in the sector. These can direct future studies on the subject in the four application areas identified and promote the development of an integrated innovation system in air transport management.